From Code to Discourse: Social Media and Linkage Mechanisms in Deliberative Systems - Benjamin A. Lyons (Journal of Deliberative Democracy)
Scholars have increasingly examined less formal conceptions of public deliberation, coinciding with a shift to the deliberative systems approach. However, few have grappled with how, or how well, discussions in distributed spaces connect to one another. Those who have theorized about such “linkage” have done so in an unsatisfactorily broad manner (Parkisnon, 2016). This article addresses this gap in the context of social media by reviewing the literature on platforms’ technical features and emergent discursive forms, and considering the capacity for these to link flows of deliberation as they evolve online and approach empowered spaces. Avenues for future research are discussed.